Low protein and methionine in blue fox diet during crowing-furring season : a field study - Koskinen, Nita; Dahlman, Tuula; Pölönen, Ilpo; Valaja, Jarmo; Rekilä, Teppo (Rus, 2005)
The feeding trial was carried out on 382 blue foxes during growing-furring period. Half of the blue foxes were males and half of them were females. The feeding trial was conducted as a field study 5.9.-14.11.2001 in private fur farm in Uusikaarlepyy, Finland (Cederholms Pälsfarm ab). The aim of this research was to study the effects of low dietary protein level with supplemented methionine on blue fox growth and fur properties in practise. The groups were control group and experimental group. Control feed contained normal protein level (recommendation of Finnish Fur Breeders Association) without amino acid supplement (commercial mink feed with 33 % protein of ME). Experimental feed contained low protein (19 % protein of ME) and supplemented methionine (2 g/kg). The control feed was made and delivered to the farm daily. The experimental feed was made once a week and stored in the farm. Both groups were fed with the same daily amount of feed. Animals were weight biweekly during the trial and they were pelted at the end of the trial. Pelt length (cm) and weight (g) was measured after which they were graded at the Finnish Fur Sales Company Ltd for colour, clarity, fur density, guard hair quality, coverage, quality and overall impression. The faeces were analysed for phosphorus, liquid nitrogen and total nitrogen. All blue foxes were healthy during the feeding trial nor did high amount of cereals cause any faecal problems. No statistically significant differences between treatments were found in mean weight gain in the trial. Final average weight per cage was 13.10 kg in control group and 13.39 kg in research group. Although specific growth rate (SGR, % per day) was better in experimental group (p<0.05). In the trial no statistically significant differences between treatments were found in pelt length, pelt weight, clarity, fur density, quard hair quality, coverage, quality and in overall impression. Blue foxes in the control group had slightly darker pelts (p<0.05). Phosphorus and nitrogen content of the faeces were much lower in the control group. In conclusion, the experiment showed that with lower dietary protein with supplemented methionine blue foxes grow normally and the pelts are the same as fed with more expensive mink feed. By using less expensive raw materials such as cereals and methionine in blue fox feed the producing costs are lower. By using less protein and ash containing raw materials in feed also phosphorus and nitrogen loads are getting smaller. Although supplemental methionine is essential in low protein feeds. Methionine is essential for hair growth. Without adequate methionine the hair growth and the skin development is abnormal. The energy content of the experimental feed was slightly lower than in control feed but still blue foxes grewsimilarly in both groups. Generally, the low dietary protein level (19% and supplemental methionine) is sufficient for growth and to produce high-quality pelts in growing-furring perioid.
Keywords: Ko; valkuainen; metioniini; kasvu; sinikettu